The Influence of Leadership Style, Team Work and Work Experience on the Performance of PT Nutrilab Pratama Jakarta Employees - Muaziz, Muaziz; Dhyan Parashakti, Ryani (Review: Journal of Multidisciplinary in Social Sciences, 2024)
Human resources are the central factor in an organization. Whatever the form and purpose, the organization is founded on a vision for the common good, and in the implementation of its mission is managed and managed by humans. Labor or employees are the most valuable resources in the organization. The phenomenon in this study is the existence of employee performance problems. Based on the observations of researchers in the field that the decline in employee performance is caused by several things, namely leadership style, team work and work experience, the purpose of this study is to analyze the effect of leadership style on employee performance. To analyze the effect of team work on employee performance. To analyze the effect of work experience on employee performance. In this research proposal using quantitative methods. Data collection using a questionnaire, made a number of questions to be filled in by respondents. The population in this study were all employees who worked at PT Nutrilab Pratama Jakarta, totaling 52 people. The sampling technique used is saturated sampling, that is, the total sample is used as a whole. The method used in this study is to use the SPSS 26.0 method Based on the results of leadership style has no effect on employee performance. team work has a positive and significant effect on performance and work experience has a positive and significant effect on performance.